El “afro” de don Fernando Ortiz y los “africanos” de Humboldt. “Afro”, “África”, Afro-Latinidad en la historia, memoria y herencia cultural de la América ibérica y el Caribe - Zeuske, Michael (HiN - Alexander von Humboldt in the Net. International Review for Humboldt Studies, 2025)
This article examines the naming of large population groups in the Americas, such as former slaves and their descendants. The group that today shapes discourse on slavery and its consequences is often called “Afros.” Not only in English-speaking countries, but also in Iberian regions (where most people were brought from Africa). The culture of these territories is referred to as “Afro-Latinidad.” This historicization examines the naming of these groups during the period of slavery (USA until 1865, Cuba until 1886, Brazil until 1888) and the invention of the term “Afro” by Fernando Ortiz (1881–1969). Ortiz’s conceptualization lends itself to comparison with Humboldt’s concepts (and ist contemporary translations). At the same time, the article traces the self-designations of those who are referred to as Afro-descendants, primarily by scholars of culture.